Internet privacy rights : rights to protect autonomy - Bernal, Paul, 1964- (Cambridge [UK] : Cambridge University Press, 2014)
What rights to privacy do we have on the internet, and how can we make them real?
4 Governments and the Symbiotic Web4.1 Tensions and balance; 4.2 Harnessing the Symbiotic Web; 5 Managing the symbiosis; 5.1 Symbiotic regulation for the Symbiotic Web; 5.2 New business models; 4 Law, privacy and the internet -- the landscape; 1 The role of law in the internet; 1.1 Cyberlibertarians and cyberpaternalists; 1.2 Network communitarians: the active community; 1.3 Law, privacy and autonomy -- and the role of rights; 2 Privacy-protective law; 2.1 Data protection and the Data Protection Directive; 2.2 Implementation and reform; 2.3 The E-Privacy Directive and the 'Cookies Directive'
Print version record.
2.4 The Cybercrime Convention and the Computer Misuse Act.
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: Data protection -- Law and legislation; Computer security -- Law and legislation; Internet -- Security measures; Internet -- Safety measures; Privacy, Right of; Internet -- Sécurité -- Mesures; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Computer security -- Law and legislation; Data protection -- Law and legislation; Internet -- Safety measures; Internet -- Security measures; Privacy, Right of; Electronic book